Beyond one-size-fits-all: Designing monetary policy for diverse models and frequencies - Alexander Dück; Fabio Verona (Bank of Finland, 2025)
We offer a contribution to the analysis of optimal monetary policy. The standard approach to determine what policy rule a central bank should follow is to take a single structural model and minimize the unconditional volatilities of inflation and real activity. In this paper, we propose monetary policy rules that perform robustly across a broad range of structural models, focusing on minimizing volatility at the frequencies most relevant for policymakers' stabilization goals. Our findings indicate that robust rules, which account for model uncertainty, advocate significantly less aggressive policy responses. Moreover, incorporating frequency-specific stabilization preferences further moderates the optimal policy actions. Ignoring model uncertainty imposes significant costs, while the cost of insuring against this uncertainty is relatively low. This cost-benefit analysis strongly supports adopting a robust-model approach to monetary policy.
urn:nbn:fi-fe202501081874
Keywords: C49; E32; E37; E52; E58; 330; monetary policy rules; policy evaluation; model comparison; model uncertainty; frequency domain; design limits; DSGE models